Afectación de la calidad de vida de los pacientes diagnosticados de rinitis alérgica atendidos en consulta externa de alergología y otorrinolaringología del Hospital Manyel Ygnacio Monteros de la ciudad de Loja. - Jaramillo Ochoa, Paula Alejandra (2017)
Allergic rhinitis is a chronic inflammatory disease of the nasal mucosa resulting from some hypersensitivity reaction type I, immunologically mediated by immunoglobulin E, with the subsequent release of inflammatory mediators, activation and cellular recruitment in response to exposure to certain allergens (pollen, mold, animal epithelium or dust mites). This study aims to determine the quality of life of patients diagnosed with Allergic Rhinitis, using the ESPRINT-15 Questionnaire, in order to establish the type of Allergic Rhinitis according to duration, gender and age group, besides to relate the type of allergic rhinitis according to duration and quality of life of the patients catered in external consultation of Allergology and Otorhinolaryngology of Manuel YgnacioMonteros Hospital of Loja city. It is a descriptive and prospective cross-sectional study that used a sample of 86 patients. It was determined that the most frequent type of rhinitis is persistent rhinitis, which in the female gender is 29.07% (n = 25), unlike the male gender that presents in 26.74% (n = 23), according to the age group, intermittent rhinitis is more frequent from 40 to 59 years old with 16.28% (n = 14); unlike persistent rhinitis, which is more common for 20 to 39 years with 20.93% (n = 18), the quality of life of patients diagnosed with Allergic Rhinitis is severe, corresponding to 59.30% ( n = 51), according to the relationship between the quality of life of patients diagnosed with Allergic Rhinitis and the rhinitis type, rhinorrhea is the highest incidence as factor, both in intermittent rhinitis with 16.28% ( n = 14); as in persistent rhinitis with 20.93% (n = 18). Key words: Allergic rhinitis, ESPRINT-15 questionnaire, quality of life